ISLAMIC EDUCATION MANAGEMENT IN AXIOLOGICAL STUDIES: THE INTEGRATION OF SCIENTIFIC AND MORAL VALUES IN LEARNING - Sunarti, Sri; Rahman, Bujang (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2025)
Abstract This study examines the integration of scientific and moral values in Islamic education from an axiological perspective, with a particular emphasis on the role of educational management in fostering holistic learners. Utilizing a qualitative research approach and a literature review method, this article analyses classical and contemporary literature related to Islamic educational philosophy, educational management, and ethical-spiritual values in education. The findings reveal that Islamic educational institutions continue to struggle with balancing cognitive achievement and character development. Fragmented curricula, inadequate value-based teacher training, and the influence of secular paradigms are identified as key factors contributing to this issue. However, the study also highlights effective integrative practices such as tauhid-based character education, value-oriented pedagogical strategies, and community engagement in the educational process. Drawing upon the philosophical insights of Al-Attas and Al-Faruqi, the study underscores the importance of a unified Islamic epistemology that harmonizes revealed knowledge (naqli) and acquired knowledge (aqli) to develop Insan Kamil—an individual who is intellectually competent, morally upright, and socially responsible. The article recommends curriculum reform, enhanced teacher development, and value-based management as core strategies to build a comprehensive and transformative Islamic education system, offering a hopeful and inspiring vision for the future of Islamic education. These findings offer valuable insights for scholars, education practitioners, and policymakers aiming to design a more sustainable, value-driven Islamic educational management system. Abstrak Penelitian ini bertujuan untuk mengkaji integrasi nilai-nilai ilmiah dan nilai-nilai moral dalam pendidikan Islam dari perspektif aksiologis, dengan penekanan khusus pada peran manajemen pendidikan dalam membentuk peserta didik yang holistik. Dengan menggunakan pendekatan penelitian kualitatif dan metode studi pustaka.  Artikel ini menganalisis literatur klasik dan kontemporer yang berkaitan dengan filsafat pendidikan Islam, manajemen pendidikan, serta nilai-nilai etika dan spiritual dalam pembelajaran. Hasil kajian menunjukkan bahwa institusi pendidikan Islam masih menghadapi tantangan dalam menyeimbangkan pencapaian kognitif dengan pembentukan karakter. Kurikulum yang terfragmentasi, minimnya pelatihan guru berbasis nilai, dan pengaruh paradigma sekuler menjadi faktor penyebab utama. Meski demikian, penelitian ini juga menemukan praktik-praktik integratif yang efektif, seperti pendidikan karakter berbasis tauhid, pendekatan pedagogis nilai-orientatif, serta pelibatan masyarakat dalam pendidikan. Dengan merujuk pada pemikiran Al-Attas dan Al-Faruqi, penelitian ini menekankan pentingnya epistemologi Islam yang menyatukan ilmu yang diwahyukan (naqli) dan ilmu yang diperoleh (aqli) sebagai dasar pengembangan insan kamil—individu yang cerdas secara intelektual, luhur secara moral, dan bertanggung jawab secara sosial. Artikel ini merekomendasikan reformasi kurikulum, penguatan pelatihan guru, serta manajemen berbasis nilai sebagai strategi utama dalam membangun sistem pendidikan Islam yang utuh dan transformatif. Temuan ini diharapkan memberikan kontribusi signifikan bagi para akademisi, praktisi pendidikan, dan pembuat kebijakan dalam merancang manajemen pendidikan Islam yang berbasis nilai secara lebih komprehensif dan berkelanjutan.